How Useful? Fish-Friendly Irrigation Guidelines for the Lower Mekong Lack Definition in Five Key Areas. - Duncan, Nicolette; Bond, Jennifer; Conallin, John; Baumgartner, Lee J. (Environmental Management, 2024)
A proliferation of irrigation infrastructure throughout the Mekong River has impacted the ability of certain fish species to migrate to fulfil their lifecycle. In response, fishways, a type of fish-friendly irrigation structure, have been developed to provide passage for these fish. In recent years, several guidelines documents providing guidance on fish-friendly irrigation structures and their construction have been published. The development process from guideline inception to publication is unclear, while their purpose, audience, and contribution to fishway practice are vague. This study is the first to review the development of three fish-friendly guideline documents, using structural criteria analysis, combined with qualitative data from 27 key informant interviews. It aimed to understand document elements such as purpose, audience, scope, and framing. The results showed reviewed guideline utility and impact could be improved by attention to five key aspects, namely: definition of target audience; engagement of target audience in guideline design; definition of guideline scope; specificity of recommendations; and evaluation. Attention to these 5 aspects may result in guidelines that are perceived as more useful by their target audience and have greater impact on water management practice.